2008
DOI: 10.1111/j.1468-1293.2008.00603.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial pneumonia in HIV‐infected patients: use of the pneumonia severity index and impact of current management on incidence, aetiology and outcome

Abstract: ObjectivesDespite a recent decrease, bacterial pneumonia (BP) is still the most common admission diagnosis in HIV patients. We analyse BP incidence, characteristics and prevention measures. MethodsObservational study of all patients hospitalized for BP in a tertiary hospital in Barcelona, Spain, from January 2000 to December 2005. Demographic and HIV-related data, BP risk factors, characteristics of BP and outcomes are analysed. ResultsOne hundred and eighty-six BP episodes in 161 patients were included; patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 30 publications
0
43
1
2
Order By: Relevance
“…It is well known that HIV-infected persons are at higher risk for IPD than the general population [4][5][6]8]. Our previous report [10] and others [4,5] have shown that rates of IPD decreased among HIV-infected patients in the early HAART era but remained higher than in the non-HIV-infected population.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…It is well known that HIV-infected persons are at higher risk for IPD than the general population [4][5][6]8]. Our previous report [10] and others [4,5] have shown that rates of IPD decreased among HIV-infected patients in the early HAART era but remained higher than in the non-HIV-infected population.…”
Section: Discussionmentioning
confidence: 96%
“…Our previous report [10] and others [4,5] have shown that rates of IPD decreased among HIV-infected patients in the early HAART era but remained higher than in the non-HIV-infected population. In the present study, we found that in the late HAART era the rates of IPD did not significantly decrease with respect to the early HAART era; this may be a result, at least in part, of the increased prevalence of HIV-infected patients with associated comorbidities, which are well known risk factors for IPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, patients with CD4 < 200 cells/µL or high severity scores would be considered severe cases. 2,10 Patient severity assessment is important for decision-making regarding the type of treatment and where the latter must be carried out. In fact, choosing the empiric treatment for bacterial pneumonia in HIV-infected patients is a great challenge, as most studies and consensus are directed at immunocompetent patients.…”
Section: Brief Communicationmentioning
confidence: 99%
“…2 The Pneumonia Severity Index (PSI) consists of interesting rules that can predict mortality in HIV-infected patients. 10 Another interting severity score is the CURB-65, adopted by the Brazilian Consensus of CAP due to its simplicity 11 (patients are considered severe when they have a score of IV or V at PSI or a score ≥ 3 at CURB-65).…”
Section: Introductionmentioning
confidence: 99%